PROFILE OF STUDENTS' CREATIVE THINKING IN INTEGRATED PHYSICS LEARNING IN ENVIRONMENTAL EDUCATION - Nurita Apridiana Lestari; Hana Fitriyah (EDUSAINS, 2023)
The ability to think creatively in physics learning is needed to help students develop creativity in finding solutions to problem-solving, especially those related to environmental education. This study aims to determine the creative thinking profile of 34 high school students in Jombang on global warming in learning that integrates environmental issues. The research was conducted using creative thinking ability test questions on global warming material, which were then analyzed descriptively and quantitatively. The results showed that students had poor scores on the elaboration indicator, while the other three indicators (fluency, flexibility, and originality) were in the moderate category. The study concluded that further research is needed to improve students' creative thinking skills at the secondary school level, especially in physics material related to the environment.